Shear bond strength of composite resin cements to ceramics - TAĞTEKİN, DİLEK (My University, 2013)
Objectives. The authors investigated the use of ceramic primers combined with self-adhesive resin composite cements on the shear bond strength (SBS) to zirconia and compared them with one conventional resin composite cement. Methods. The authors divided zirconia substrates (N = 550) into three groups: RelyX Unicem Aplicap self-adhesive universal resin composite cement (3M ESPE, St. Paul, Minn.) (group A) (n = 220); G-CEM Capsule selfadhesive resin composite cement (GC Europe, Leuven, Belgium) (group B) (n = 220); and Panavia 21 with Clearfil Porcelain Bond Activator and Clearfil SE Bond primer (n = 110) (Kuraray Dental, Tokyo) used as a standard comparison (SC). The authors examined the self-adhesive resin composite cements without (0) and with (1) the use of a ceramic primer. They measured SBS initially (37°C for three hours), after water storage (37°C for one, four, nine, 16 or 25 days) and after thermal cycling (5°C and 55°C for 1,500, 6,000, 13,500, 24,000 or 37,500 cycles). The authors analyzed data by using descriptive statistics, the Mann-Whitney test, the Kruskal-Wallis test and a c2 test. Results. Application of a ceramic primer did not result in a negative impact on SBS. Specimens in the A1 group (that is, RelyX Unicem Aplicap with ceramic primer) exhibited significantly higher SBS before and after water storage and thermal cycling compared with specimens that were not treated with a primer. The self-adhesive resin composite cements combined with ceramic primer exhibited similar or higher SBS values compared with those in the SC group at each aging duration (that is, water storage and thermal cycling). With respect to G-CEM Capsule, the authors observed a significantly positive effect of the primer after nine and 16 days’ water storage and after one and four days’ thermal cycling. They observed predominantly adhesive failures. Conclusions. Ceramic primer in combination with self-adhesive resin composite cement demonstrated a positive effect on SBS to zirconia and should be used for cementation. Practical Implications. Long-term adhesion to ceramic plays an important role in the longevity of dental restorations. Therefore, the authors recommend that clinicians use a ceramic primer when cementing zirconia restorations.
Keywords: Zirconia; bonding properties; zirconia primer; self-adhesive cements